Business model evolution for ITS services - Kostiainen, J.; Zulkarnain; Leviakangas, Pekka; Hautala, R. (2013)
While the global economy has suffered in the recent years and projections for the future are highly uncertain, Intelligent Transport Systems and Services (ITS) is one of the sectors where growth potential is still envisaged and has shown to be growing in steeper curves than other industry sectors. Evaluating the roles and shares of different stakeholders is challenging due to the involvement of several public and private actors, which complicates the business model value network. The roles in value networks change with the emergence of new business models and technology. With concepts such as open data, open source, and cloud computing, the changes can be dramatic. This paper examines existing business models and, based on those, presents both traditional and modern versions of a generalised business model framework.